Developing human resources during organizational transition: An inductive case study of a corporate acquisition - Patricia Scescke Slama (Adult Education Research Conference, 1993)
Corporate acquisitions cause considerable trauma, for individual employees as well as organizations as a whole. An awareness of the predictable stages of transition can assist in identifying the timing of appropriate strategies.